Pengaruh Total Quality Management Terhadap Kinerja Perusahaan Melalui Mediasi Perilaku Produktif Karyawan - Septyani Rosediana; Jauhari Arifin (Peneliti.net, 2022)
Industrial world development makes companies have to do a lot of improvisation to achieve the company's final output that is in line with the company's vision and mission. PT. Nusa Toyotetsu Corp. is a company engaged in the manufacturing industry and produces various kinds of car spare parts. The purpose of this study is to identify the effect of Total Quality Management on company performance, identify the effect of Total Quality Management on employee productive behavior, and identify Total Quality Management on company performance through mediation of employee productivity. Research data collection was carried out by distributing questionnaires to employees of PT. Nusa Toyotetsu Corp. Total Quality Management has a positive significant effect on employee productive behavior of 0.498, so H1 is accepted. Total Quality Management on the company's performance directly has a significant positive effect of 0.746 so that H2 is accepted. The effect of employee productive behavior on employee performance results in tcount which is smaller than ttable, then H3 is rejected. H4 for indirect effects using mediation in the form of employee productive behavior on Total Quality Management with employee performance accepted.